RESPON TANAMAN KEDELAI (Glycine max L. Merril) TERHADAP DOSIS PUPUK KALIUM DAN WAKTU APLIKASI PUPUK NITROGEN - Todung Barita Radja Siregar; Aslim Rasyad; Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Adequate supply of nutrient by fertilizer are generally believed to improve soybean yield especially when it is grown in suboptimal soil condition. In this study we grew a soybean variety and fertized them with N and K fertilizer to determine the response of the variety to the time of N application and the rate of K fertilizer. A field experiment was conducted in Agriculture Experiment Station near Pekanbaru by using a randomized completely block design with 3 replications. The rate of potassium fertilizer were 25 kg K2O per ha, 50 kg K2O per ha and 75 kg K2O per ha while the time of N application were 25 kg N per ha at planting date, 25 kg N per ha at 30 days after planting and 25 kg N per ha at planting and add another 25 kg N per ha at 30 days after planting. Seed were planted with a rate of 30 cm by 20 cm in a plot of 3 m length and 2 m wide in 2017. Parameters observed were plant height, number of main branches, plant growth rate, leaf area index, flowering date, harvest date, number of filled pods per plant, seed weight per plant, seed yield per m2, weight of 100 seeds and harvest index. The results showed that application of N fertilizer affected leaf area index, number of filled pods, seed weight per plant, and grain yield per m2, however, the rate of K fertilizer only affected plant growth rate and leaf area index but did not for others characters. The treatment combinations indicated the significant effect on number of main branches and seed yield per m2, where the application of N 25 kg per ha at planting followed at the same rate at 30 days after planting and adding by 50 kg per ha K2O gave greater number of main baranches and more grain yield per m2. Keywords : nitrogen aplication, potassium fertilizer, yield components, growth rate